KOMUNIKASI INTERPERSONAL ANTARA IBU DAN ANAK YANG MENGHADAPI MENARCHE DI SDN Â CENTONG DESA CENTONG KECAMATAN Â GONDANG KABUPATEN MOJOKERTO - Saudah, Noer; Wahyuningrum, Tria (JURNAL KEPERAWATAN SEHAT, 2015)
At the age of 10-14 years there has been a physical change which is characterized by the occurrence of menarche which is the first experience for girls, so it requires an understanding and knowledge of menarche, so as not to be psychic emergence negative reactions, during first menstruation. Interpersonal communication between children and mothers is helpful in understanding, the changes that occur in adolescent girls. The purpose of this study is to describe the interpersonal communication between mother and child who face menarche at SDN Centong, Centong Village, District Gondang, Mojokerto. Design of this research using descriptive method. The population in this study is all girls grade IV, V, and VI, which face menarche, which amounted to 55 respondents. Samples numbered 55 respondents, taken using total sampling. Data sources using primary data, the instruments using questionnaire that distributed to respondents. Data were analyzed using descriptive analysis with frequency distribution. The result showed, almost all respondents said that interpersonal communication with her mother in the medium category as many as 42 respondents (76.4%). Respondents usually do communication with parents at certain times because many of them still feel shame and fear while communicating with her mother about menstruation problems. Mother, should provide sufficient time for communication in children, to discuss childrens issues, particularly reproductive health problems, associated with menstruation so that children do not feel afraid to face the changes that occur.Keywords: Interpersonal Communication, Mother And Child, Menarche